Astrocyte Reactivity Following Blast Exposure Involves Aberrant Histone Acetylation - Bailey, Zachary S.; Grinter, Michael B.; VandeVord, Pamela J. (Frontiers in Molecular Neuroscience, 2016)
Blast induced neurotrauma (BINT) is a prevalent injury within military and civilian populations. The injury is characterized by persistent inflammation at the cellular level which manifests as a multitude of cognitive and functional impairments. Epigenetic regulation of transcription offers an important control mechanism for gene expression and cellular function which may underlie chronic inflammation and result in neurodegeneration. We hypothesize that altered histone acetylation patterns may be involved in blast induced inflammation and the chronic activation of glial cells. This study aimed to elucidate changes to histone acetylation occurring following injury and the roles these changes may have within the pathology. Sprague Dawley rats were subjected to either a 10 or 17 psi blast overpressure within an Advanced Blast Simulator. Sham animals underwent the same procedures without blast exposure. Memory impairments were measured using the Novel Object Recognition (NOR) test at two and seven days post-injury. Tissues were collected at seven days for Western blot and immunohistochemistry analysis. Sham animals showed in-tact memory at each time point. The novel object discrimination decreased significantly between two and seven days for each injury group (p<0.05). This is indicative of the onset of memory impairment. Western blot analysis showed glial fibrillary acidic protein (GFAP), a known marker of activated astrocytes, was elevated in the prefrontal cortex (PFC) following blast exposure for both injury groups. Analysis of histone protein extract showed no changes in the level of any total histone proteins within the PFC. However, acetylation levels of histone H2b, H3, and H4 were decreased in both groups (p<0.05). Co-localization immunofluorescence was used to further investigate any potential correlation between decreased histone acetylation and astrocyte activation. These experiments showed a similar decrease in H3 acetylation in astrocytes exposed to a 17 psi blast but not a 10 psi blast. Further investigation of gene expression by PCR array, showed dysregulation of several cytokine and cytokine receptors that are involved in neuroinflammatory processes. We have shown aberrant histone acetylation patterns involved in blast induced astrogliosis and cognitive impairments. Further understanding of their role in the injury progression may lead to novel therapeutic targets.